Design of Resistivity Meter Data Storage System Based on Arduino Mega 2560 Laboratory Scale Measurement Results - Dewa Gede Eka Setiawan; Rizky Prayatman; Salmawaty Tansa (Department of Physics, Sebelas Maret University, 2024)
A resistivity meter can find out resistivity depth of rock structure, sediment layer, or the depth of water surface. However, the resistivity meter that is often used requires manually recording of the measurement results before inputting them into the processing data software, and this creates many steps in the geoelectric survey. This is because acquiring a resistivity meter with a data storage system entails additional costs, due to its expensive price. Consequently, many of the resistivity meters currently found in laboratories or used in the field are not equipped with a data storage system. This research aims to design a resistivity meter with a data storage system for measurement results, based on Arduino Mega 2560, for laboratory scale. The used sensors were INA219 currents sensor and voltage sensor. In addition, the tests were carried out to determine the level of accuracy of each sensor and testing for data storage system of measurement result. This research employed Schlumberger configuration in the development of resistivity meter. This research has successfully developed a resistivity meter device with a current sensor accuracy level of 97.28% using the INA219 sensor, and a voltage sensor accuracy level of 97.44%. It is noteworthy that the accuracy level is high, and the device is capable of performing readings effectively. This research has successfully designed a resistivity meter which has a measurement data storage.